Pelatihan Membangun Mental Kewirausahaan bagi Anggota Aisyiyah di Desa Kembaran, Banyumas, Jawa Tengah - Widhiandono, Hengky; Suyoto, Suyoto; Setiyabudi, Ragil; Priyanto, Eko (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
There are still many poor people in Indonesia who need solutions through improving family welfare for reducing the negative impact of conditions from community poverty. Expansion of the role of the women/wife in a family is one of the keys because when the income’s husband is not sufficient, women/wives can help to increase the income’s family. There are many examples of reality from successful women entrepreneurs. One of the women’s organizations is Aisyiyah. The Aisyiyah aims to empower their member without leaving a nature woman's life. Based on a survey, there are many potentials of women for business at home that have not been optimally developed, so they need to get training about mental entrepreneurship so that women entrepreneurs with reliable. The method of training is carried out with an attractive presentation about the real story of a successful entrepreneur and with deep expression in communication techniques and added problem-solving sessions for solutions to the participants' problems of business, especially the mental of entrepreneurship. The training has been carried out for 2 hours and consists of the topic about mentality entrepreneurship and its problem solvings. The materials of training include techniques of self-motivation and other people, the concept of successful business, healthy products, and positive mental thinking. The evaluation of the training results in the post-test showed a score of 7.75 out of 10 on a scale of points. The level of satisfaction from the training process can be seen from the questionnaire responses from participants with the rank of 4th highest frequency from respondents, namely: obtain entrepreneurial knowledge, interesting material, self-motivated business, and get friend to network business. The lacks of training are majority want additional training time.Masih banyak masyarakat miskin di Indonesia yang membutuhkan solusi melalui peningkatan kesejahteraan keluarga untuk mengurangi dampak negatif kondisi dari kemiskinan masyarakat. Perluasan peran wanita/istri dalam keluarga menjadi salah satu kuncinya karena ketika pendapatan suami tidak mencukupi, wanita/istri dapat membantu meningkatkan pendapatan keluarga. Ada banyak contoh kenyataan dari pengusaha wanita sukses. Salah satu organisasi perempuan adalah Aisyiyah. Aisyiyah bertujuan untuk memberdayakan anggotanya tanpa meninggalkan kehidupan wanita kodrat. Berdasarkan survei, masih banyak potensi wanita untuk usaha di rumah yang belum dikembangkan secara optimal, sehingga perlu mendapatkan pelatihan tentang mental entrepreneurship agar wanita wirausaha dengan handal. Metode pelatihan dilakukan dengan presentasi yang menarik tentang kisah nyata seorang wirausahawan yang sukses dan dengan ekspresi mendalam dalam teknik komunikasi dan ditambah sesi pemecahan masalah untuk solusi atas masalah bisnis peserta, terutama mental kewirausahaan. Pelatihan telah dilaksanakan selama 2 jam dan terdiri dari topik tentang mentalitas kewirausahaan dan pemecahan masalahnya. Materi pelatihan meliputi teknik motivasi diri dan orang lain, konsep bisnis sukses, produk sehat, dan mental positif. Evaluasi hasil pelatihan pada post-test menunjukkan skor 7,75 dari 10 skala poin. Tingkat kepuasan dari proses pelatihan dapat dilihat dari angket tanggapan dari peserta dengan peringkat ke-4 frekuensi tertinggi dari responden, yaitu: memperoleh pengetahuan kewirausahaan, materi yang menarik, bisnis yang memotivasi diri, dan mendapatkan teman untuk bisnis jaringan. Kekurangan pelatihan adalah mayoritas menginginkan waktu pelatihan tambahan.